2020
DOI: 10.1017/s1366728920000498
|View full text |Cite
|
Sign up to set email alerts
|

Sentence repetition with bilinguals with and without DLD: Differential effects of memory, vocabulary, and exposure

Abstract: Though previous research has shown that sentence repetition (SR) is an informative tool for identifying developmental language disorder (DLD) in bilinguals, little is understood about the skills that underlie children's performance on the task. With a population of 136 school-age Spanish–English bilinguals, the present study explores the contribution of verbal short-term memory, vocabulary, and language exposure on two SR tasks developed in English and Spanish. Results indicate that these skills may differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 73 publications
(127 reference statements)
0
13
0
4
Order By: Relevance
“…Nevertheless, SR tasks are considered as a useful tool that has been used in order to distinguish bilingual children with typical development from children with atypical development. In particular, Pratt et al (2020) investigated the extent to which verbal short-term memory, vocabulary, and language exposure have an influence on two SR tasks conducted both in English and in Spanish, testing 136 school-age Spanish–English bilinguals. The findings demonstrate a difference in SR performance between typically developing children and children with Developmental Language Disorder (DLD) with regard to the effect of the aforementioned skills.…”
Section: Sr and Language Experiencementioning
confidence: 99%
“…Nevertheless, SR tasks are considered as a useful tool that has been used in order to distinguish bilingual children with typical development from children with atypical development. In particular, Pratt et al (2020) investigated the extent to which verbal short-term memory, vocabulary, and language exposure have an influence on two SR tasks conducted both in English and in Spanish, testing 136 school-age Spanish–English bilinguals. The findings demonstrate a difference in SR performance between typically developing children and children with Developmental Language Disorder (DLD) with regard to the effect of the aforementioned skills.…”
Section: Sr and Language Experiencementioning
confidence: 99%
“…For example, Redmond et al (2019) found that individually administered screens involving sentence repetition and past-tense elicitation tasks have high sensitivity and specificity against a range of reference standards for language impairment (see also Archibald & Joanisse, 2009). Whereas Redmond et al's study focused on monolingual English speakers, Pratt et al (2020) demonstrated the utility of sentence repetition tasks as a screen for language impairment in bilingual Spanish-English students (see also Gutiérrez-Clellen et al, 2006). Adlof et al (2017) and Hendricks et al (2019) have demonstrated the potential of group-administered screenings using sentence-picture matching tasks for identifying language impairment within samples that included speakers of mainstream and nonmainstream dialects of American English, although the sensitivity and specificity for the group-administered tasks were lower than those achieved with individually administered measures in the work of Redmond et al In some situations, the benefits in terms of screening efficiency may outweigh the costs of reduced classification accuracy of group screening instruments.…”
Section: Universal Screeningmentioning
confidence: 99%
“…For this task, children are asked to repeat sentences verbatim and receive scores based on the accuracy of their repetitions. There is strong evidence for the validity of sentence repetition tasks as measures of morphosyntactic ability for children who speak multiple languages (Fitton et al, 2019 ; Pratt et al, 2021 ). The BESA Sentence Repetition subtest has high internal consistency ( a =0.96 in Spanish and a =0.95 in English).…”
Section: Methodsmentioning
confidence: 99%